Assessing the Approaches to Learning of Twinning Programme Students in Malaysia - Choo, Pauline Goh Swee (Malaysian journal of learning & instruction, 2006)
The study set out to examine the psychometric properties of the scores obtained on the modified 20-item Revised Two Factor Study Process Questionnaire (R-SPQ-2F). The study also investigated the relationship between scores on the R-SPQ-2F and students’ learning-related outcomes. In addition, it also examined for any relationships among student’s background variables of gender, choice of academic discipline, age, English language competency, approaches to learning, and learning-related outcomes. Data based on responses of 368 Malaysian students undertaking the twinning mode of study showed the modified R-SPQ-2F to be reliable and factorially valid. The findings also found deep approaches to learning were positively related to students’ learning-related outcomes, while surface approaches to learning were negatively associated. Students’ background characteristics such as choice of academic discipline and English language competency, and approaches to learning were good predictors of students’ learning-related outcomes.